Parenting From the Outside-In: A Paradigm Shift in Parent Training? - Mazzucchelli, Trevor; Sanders, M. (Australian Academic Press Pty Ltd, 2014)
It has recently been asserted that a paradigm shift is emerging in the delivery of parenting programs. Specifically, it has been suggested that interventions from the field of interpersonal neurobiology represent sophisticated alternatives to positive parenting interventions based on social learning models and behavioural principles, and better reflect how contemporary practitioners consider parenting. We examine this assertion, dispel a number of myths, and conclude that characterisations of positive parenting programs are frequently misleading and do not adequately reflect contemporary models of practice. There is little justification to support the claim that the field should abandon this ‘paradigm’. Indeed, there has been a considerable expansion in the evidence base supporting positive parenting programs and the emergence of a public health framework that blends universal and indicated interventions that can greatly increase the reach and lower the costs of delivering parenting interventions.